Technology spillovers and outside options in a bilateral duopoly - Noriaki Matsushima; Laixun Zhao (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This paper examines the role of outside options in a downstream duopoly with exclusive vertical relations as in the Japanese automobile industry. In our setup, the downstream firms have outside options, and two upstream firms with exclusive relations can engage in cost reducing investments. More interestingly, each upstream firm can choose whether to voluntarily generate technology spillovers to its rival. We show that better outside options of the downstream firms can induce voluntary technology spillovers in the upstream level, increasing the profits of all firms on the vertical chain.
Keywords: L13; O32; M11; C72; 330; Strategic sourcing; Outside option; Spillovers; Vertical relations